Laboratory demonstrators' perceptions of the remote laboratory implementation of a fluid mechanics laboratory - Sarukkalige, Ranjan; Lindsey, Euan; Anwar, Faisal (Australasian Association for Engineering, 2010)
Remote laboratories are a mature technology that is becoming increasingly prevalent in the delivery of undergraduate engineering degree programs. Acceptance by teaching staff is important in order for remote laboratories to gain widespread support, however existing efforts have overlooked the perspective of the demonstrators who supervise the laboratory classes. This paper investigates the responses of five laboratory demonstrators to the conversion of a fluid mechanics laboratory to the online mode of delivery. The demonstrators’ responses were largely positive towards the shift to remote access, with a clear feeling that the online mode would be better for them as demonstrators. The demonstrators did express concerns, however, that the learning experience of their students could be compromised by the alternative access mode.